(untitled) - Charles ([Carlsbad, Calif.], 2007)
The Elements of organic gardening is a practical guide to organic gardening as practiced at Highgrove and The Prince of Wales’s two other gardens: Clarence House in London and Birkhall in Scotland"--Provided by publisher.
Keywords: Organic gardening; Great Britain